(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this paper, the context and characteristics of the political violence during the 1970s related to the actions of the com- pany Ledesma (province of Jujuy, Argentina) are discussed. In the context of prosecution of corporation crimes against humanity, we propose two related research lines. One is an approach to the main features of social, economic and poli- tical context of Jujuy and Ledesma company around 1970, the other being an analysis on both the judicial and social validation process. Debates on the validation of knowledge about past and present times will be developed, based on the importance of the “true” story of Ledesma and “distor- tions” of memories.